Secondary sclerosing cholangitis in critically ill patients with febrile infection-related epilepsy syndrome (FIRES): a case series - Muccioli, Lorenzo; Di Vito, Lidia; Pasini, Elena; Ferri, Lorenzo; Vitale, Giovanni; Granito, Alessandro; Mostacci, Barbara; Moneti, Manuel; Licchetta, Laura; Liguori, Rocco; Tinuper, Paolo; Castioni, Carlo Alberto; et al. (Frontiers in Neurology, 2025)
ObjectivesTo describe the occurrence of secondary sclerosing cholangitis in critically ill patients (SC-CIP) with febrile infection-related epilepsy syndrome (FIRES).MethodsMonocentric retrospective analysis of all adult patients with FIRES admitted from January 2020 to December 2024.ResultsFour patients (3 males) with a mean age of 24 years (range: 18–40 years) and no significant medical history presented with cryptogenic FIRES. They required treatment with antiseizure medications (mean: 9; range: 8–10), anesthetics (propofol, midazolam and ketamine in all cases), and immunotherapies. The average duration of status epilepticus (SE) was 57 days (range: 34–90 days), while the mean duration of intensive care unit (ICU) stay was 82 days (range: 58–117 days). All patients developed cholestatic liver disease during their ICU stay, reversible in one case. In the three cases with persistent injury (75%), SC-CIP was diagnosed with MR-colangiography after a mean of 106 days from SE onset.DiscussionThe high incidence of SC-CIP in our cohort of patients with FIRES suggests a link between these two rare conditions, likely related to prolonged intensive care, hyperinflammation and polytherapy, including ketamine use. Vigilant monitoring of liver disease progression in critically ill patients with FIRES and similar predisposing factors may allow early recognition of SC-CIP and improved patient outcomes.